Influenced Factors Of E-Money Adoption - Farid Nurhidayat (JRAK: Journal of Accounting Research and Computerized Accounting, 2018)
This research aims to identify the factors that influence the adoption of e-money in Yogyakarta, Jakarta and Surabaya. It also aims to test formed model of e-money adoption through some variables; perceived of usefulness, perceived ease of use. There are 300 people from Jakarta, Surabaya and Yogyakarta as research samples. Data analysis used here is Structural Equation Model (SEM). Research result shows that the factors which influenced e-money adoption are subjective norm, perceived usefulness and perceived ease of use. This model is able to clarify the connection among influenced factors of e-money adoption. The implication of the research result to the publisher who provide e-money is to perceived usefulness and perceived ease of use factors, so it will gain more trust from every people to adopt e-money